Exocyst Sec10 is Involved in Basolateral Protein Translation and Translocation in the Endoplasmic Reticulum - Choi, Soo Young (2012)
BACKGROUND: Protein translation and translocation at the rough endoplasmic reticulum (RER) are the first steps in the secretory pathway. The translocon through which newly-made proteins are translocated into or across the RER membrane, consists of three main subunits, Sec61α, β, and γ. Sec61β facilitates translocation, and we and others showed that the highly-conserved eight protein exocyst complex interacts with Sec61β. We also showed that the exocyst was involved in basolateral, and not apical, protein synthesis and delivery. Recently, however, exocyst involvement in apical protein delivery was reported. Furthermore, we showed that the exocyst was necessary for formation of primary cilia, organelles found on the apical surface. METHODS: GST pulldown was performed on lysate of renal tubule cells to investigate biochemical interactions. Cell-free assays consisting of cell-free extracts from rabbit reticulocytes, pancreatic ER microsomal membranes, transcripts of cDNA from apical and basolateral proteins, ATP/GTP, amino acids, and (35)S-methionine for protein detection, were used to investigate the role of the exocyst in synthesis of polarized proteins. P(32)-orthophosphate and immunoprecipitation with antibody against Sec61β was used to investigate the Sec61β phosphorylation in exocyst Sec10-overexpressing cells. RESULTS: Sec10 biochemically interacts with Sec61β using GST pulldown. Using cell-free assays, there is enhanced recruitment to ER membranes following exocyst depletion and basolateral VSVG protein translation, compared to apical HA protein translation. Finally, Sec10 overexpression increases Sec61β phosphorylation. CONCLUSION: These data confirm that the exocyst is preferentially involved in basolateral protein translation and translocation, and may well act through the phosphorylation of Sec61β.